Money and exchange rates in the Grossman-Weiss-Rotemberg model - Alvarez, Fernando 1964-; Atkeson, Andrew 1961- (1996)
We examine the impact of monetary injections in the Grossman-Weiss-Rotemberg Model and show that monetary shocks can lead to nominal exchange rates that are more volatile than inflation, money growth or interest rate differentials. Moreover, movements in real exchange rates following monetary injections can be persistent and nearly as large as movements in nominal exchange rates nominal exchange rates.
Keywords: Ökonometrisches Modell; Foreign exchange rates -- Econometric models; Interest rates -- Econometric models; Money supply -- Econometric models